Fatigue in multiple sclerosis: Why is it so difficult to manage? - Iulia Monica Bogdan; Mara Cercignani; Waqar Rashid (Advances in Clinical Neuroscience & Rehabilitation, 2017)
This review aims to inform clinicians about the current strategies in managing fatigue in multiple sclerosis (MS) and the challenges which arise from the insufficient understanding of the underlying mechanisms. It gives an overview of the research undergone to find symptomatic treatment, the non-pharmacological approaches and the scarce knowledge about the impact of disease modifying treatment on fatigue in MS. Finally, it presents a few recent hypotheses and underlines the importance of finding a framework which brings together knowledge in the field.